A identidade do Brock 1985-1990 - Paiva, Marília Luana Pinheiro de (2016)
The research sought to understand the discursive processes that permeated the identity of the Brazilian rock (1985-1990) from the lyrics of these songs on the "hit parade reader" of Bizz magazine. The research had as main source of study the Bizz magazine, which had its August 1985 time period until mid-2007, is considered a major journal for being a rock genre movement of the vehicle in the national and international level and the his long stay in business. Thus, we selected 6 songs for discourse analysis from the 66 copies of the magazine Bizz between the years 1985-1990, during which happens the re-democratization of Brazil, so choosing one every year. In this perspective, the central axis of the research was to try to understand what identity present in the Brazilian rock, taking into account the historical and social context in which these songs were inserted. He attempted to interpret and analyze historically the Brazilian musical context, realizing that the analyzed rock bands built an identity in relation to the political period in which they were inserted (1985-1990). The work addressed the beginning of rock in Brazil in the mid 1950s, with the movement of the Young Guard, through Tropicália, MPB, punk rock and rock in the 80s he was noticed then the spread of the Brazilian rock in the 1980s due to political openness and the democratization process. It was found that with the softened censorship, created a larger space for socialization and impact of rock with the advent of Rock in Rio. The songs analyzed in this research have recognized a cultural identity in relation to the immediate historical context. the authors Stuart Hall were used (2011), Zygmunt Bauman (2005) and Sandra Jatahy Pesavento (1995) to understand the identity of the bands, its conceptual aspects, and also used the authors Michael Maffesoli (2000) and Barbara Rosenwein (2011) to understand the concepts of tribes and communities that formed in the 1980s in the survey, we used the theoretical analysis of the French Discourse, which, according to Eni Orlandi (2005), refers to the practice of language as production of meanings and aims to understand the place of interpretation of the subject and its reality. The Discourse Analysis assists thus in reflection on the social practice, political, ideological and historical aspects, allowing then a thorough approach to the discursive processes. In this sense, the study addressed the letter of the songs as a source for understanding social and ideological sets that permeated the history of Brazil in the democratization period. It was understood, so that the bands studied here created their own cultural identity, through the letters of politicized music and his irreverent character to the 1980s.